The Case of Dr George Gale V. the College of Physicians and Surgeons of Ontario: A Legal Analysis - Matthew Wilton (Pain Research and Management)
On March 15, 2002, anaesthetist and pain practitioner, Dr George Gale, had his license to practice medicine in Ontario revoked by a decision of the Discipline Committee of the College of Physicians and Surgeons of Ontario (CPSO) (1,2). To that point, Dr Gale had practiced medicine as an anaesthetist in Ontario without incident. The CPSO Discipline Committee hearing had taken place over 22 days in 2001 and 2002. The focus of the CPSO prosecution against Dr Gale was his pain practice conducted at a well-known pain clinic in Toronto, Ontario. By an Ontario Divisional Court decision dated October 10, 2003, the CPSO Discipline Committee decision was set aside on appeal (3). Most importantly, the Ontario Divisional Court held that the penalty of revocation levied against Dr Gale was unfair and based on several serious errors made by the Discipline Committee. A closer examination of the decisions of both the Discipline Committee and the Ontario Divisional Court will hopefully illustrate both the medical standards of practice issues for pain practitioners, and some of the perils created by the self governing activities of the CPSO. To put the Gale decision in proper context, it will be necessary for us to briefly examine the function of the CPSO and its Discipline Committee.